AKTIVITAS ANTIFUNGI EKSTRAK DAUN KEDONDONG (SPONDIAS PINNATA) DALAM MENGHAMBAT PERTUMBUHAN ASPERGILLUS FLAVUS - Fitriani, Silvia (LenteraBio: Berkala Ilmiah Biologi, 2013)
People believe that stems, fruits, and leaves of kedondong plants (Spondias pinnata) are useful as a traditional medicine, such as the leaves and the fruit can be used as a cough medicine and the bark part can be used as a diarrhoea medicine. This research aimed to describe the antifungal activities kedondong leaves extract to inhibition on the growth of Aspergillus flavus and determine the effective concentration of kedondong leaves extract on inhibiting the A. flavus growth. The research were designed by randomized completely design with one factor treatment, namely concentration of the kedondong leaves extract with 4 replications. Antifungal activity test to be used solid dilution method. Kedondong leaves extract solution to be used with final concentration of 0%, 4%, 6%, 8%, 10% w /v. Observation was conducted after incubation for 7 days at room temperature. The parameters observed was the inhibition A. flavus growth with indicated size of the diameter mycelial colony. The results showed that the kedondong leaves extract had an inhibitory effect on mycelial colony A. flavus growth. Concentration 8% and 10% were effective concentration to inhibit the growth of mycelial colony A. flavus. Concentration 8% inhibition diameter mycelial colony A. flavus was 1.65 ± 0.2 cm with the inhibition potency of 77.82% and 10% concentration inhibtion diameter of mycelial colony A. flavus was 1.46 ± 0.2 cm with the inhibition potency of 80.37%. Research showed that the higher concentration of antifungal gave the smaller average diameter mycelial colonies and the greater percentage of the inhibition potency.